A Discontinuous Individual Growth Model of Swimming Crab Portunus trituberculatus and Its Application in the Nutrient Dynamic Simulation in an Intensive Mariculture Pond - Dong, Shipeng; Xu, Xian; Lin, Fan; Yu, Liye; Shan, Hongwei; Wang, Fang (Frontiers in Marine Science, 2022)
Environmental problems such as organic pollution and eutrophication caused by highly intensive mariculture activities constrain the sustainable and healthy development of industry. Therefore, it is necessary to quantify the nutrient dynamics of aquaculture animals in order to reduce the risk of environmental pollution. In this study, a discontinuous individual growth model of Portunus trituberculatus in an intensive mariculture pond of P. trituberculatus–Penaeus japonicus–Sinonovacula constricta was constructed based on a dynamic energy budget theory combined with the index of condition factor. This model better predicted the growth and molting behavior of P. trituberculatus, and an acceptable fit was obtained through model parameterization using the Add-my-Pet (AmP) method (mean relative error = 0.058, symmetric mean squared error = 0.007). Ten molts were simulated over 180 days and generally coincided with the recorded molt time points. Based on this model and P. trituberculatus populations, the dynamic processes of carbon, nitrogen, and phosphorus in ingestion, respiration, excretion, feces, residual feed, dead crabs, seeding, molt, and harvest were simulated. The carbon, nitrogen, and phosphorus ingested during the 180-day culture period were 4,938.57 kg ha-1, 1,255.88 kg ha-1, and 244.16 kg ha-1, respectively. Carbon, nitrogen, and phosphorus removal by harvest accounted for 1.06%, 1.03% and 0.62% of the total ingestion, respectively, while carbon, nitrogen, and phosphorus removal by dead crabs accounted for 6.84%, 6.63%, and 4.04%, respectively, and carbon, nitrogen, and phosphorus released from residual feed into the water accounted for 41.43% of the total feed. The accurate simulation of molting behavior and nutrient dynamics in this study provides a theoretical basis for molting risk prevention and environmental stress assessment of P. trituberculatus and provides basic modules and data support for the construction of the integrated mariculture ecosystem model.